2022
DOI: 10.1111/1556-4029.15023
|View full text |Cite
|
Sign up to set email alerts
|

Incestuous childhood sexual abuse between siblings resulting in pregnancy without sexual intercourse

Abstract: Victims of incest are usually women and children who are mostly girls. The abuse between siblings may remain hidden because of the family's fear of social stigma, though it may result in pregnancy. This article presents a case of incestuous childhood sexual abuse between siblings resulting in pregnancy without intercourse, an event rarely reported in the literature. An 11-year-old girl was brought to the hospital because of How to cite this article: Eroglu İ, Yildiz A, Seviçin S. (2022).Incestuous childhood se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…When the sexual abuse was in the form of incest, previous studies reported that psychiatric disorders were seen more often [6, 14, 37–40]. Similarly, in the current study, in cases where there was an incestuous relationship, the frequency of psychiatric diagnosis was determined to be significantly high ( p = 0.025).…”
Section: Discussionsupporting
confidence: 65%
“…When the sexual abuse was in the form of incest, previous studies reported that psychiatric disorders were seen more often [6, 14, 37–40]. Similarly, in the current study, in cases where there was an incestuous relationship, the frequency of psychiatric diagnosis was determined to be significantly high ( p = 0.025).…”
Section: Discussionsupporting
confidence: 65%